معالم الوعي السنني في المشروع الإصلاحي عند عبد الحميد بن باديس - مخلوف, مصطفى (جامعة الوادي university of eloued, 2023)
ملخص: هذه الدراسة هي محاولة للكشف عن بعض معالم الوعي السنني في المشروع الإصلاحي عند عبد الحميد بن باديس بصفته أحد رواد حركة التجديد الحضاري الحديث. معتمدا في ذلك على المنهج الوصفي والتحليلي، وقد جاءت الدراسة في ثلاثة مباحث: تطرق في أولها إلى بيان مفهوم الوعي السنني وعلاقته بالإصلاح، أما المبحث الثاني فبين فيه معالم السنن الإلهية في فكر ابن باديس، وتناول في المبحث الثالث تجليات تعامل ابن باديس مع السنن الإلهية وإعمالها في مشروعه الإصلاحي، ليخلص البحث بخاتمة عرض فيها نتائج الدراسة، أهمها: أن السنن الإلهية كان لها ظهور متميز في المشروع الإصلاحي الباديسي تنظيرا وممارسة، وأن استحضار هذا المنهج الإصلاحي قمين بإعادة بعثه وتفعيله في عمليات الإصلاح الحديثة للمجتمع والأمة، وأن فقه السنن الإلهية في الإصلاح ضرورة منهاجية لتوجيه وترشيد مشاريع الإصلاح وبعث فاعليتها الحضارية. Abstract : This studyis an attempt to uncover some of the milestones of Law consciousness in the reform project of Ibn Badis being one of the pioneers of the modern civilizational renewal movement.to cusing On the descriptive and analytical approach, the study came in three sections : In the first section he explained the concept of law consciousness and its relation with the reform. The second showed the features of the divine laws .while the third section showed Ibn Badis, dealings with the divine law and its implementation in his reform project. The study resulted the following : divine laws had a distinctive appearance in Ibn Badis'reform project bath theoritically and practically, and that the invocation of this reform approach was worth reviving and activating in the modern reform processes effectivating the society and the nation, and that divine laws in the reform is a systematic necessity to guide and rationalize reform projects and to revive their civilizational effective ness
مقال
Keywords: السنن الإلهية؛ الإصلاح؛ عبد الحميد بن باديس